Benzo[a]pyrene stimulates miR-650 expression to promote the pathogenesis of fatty liver disease and hepatocellular carcinoma via SOCS3/JAK/STAT3 cascades. (27th August 2021) - Ge, Yang; Gu, Pengfei; Wang, Wenbo; Cao, Liyuan; Zhang, Lulu; Li, Jingquan; Mu, Wei; Wang, Hui
: Modern diets, which often feature high levels of fat and charcoal-grilled meat, contribute to the pathogenesis of obesity and non-alcoholic fatty liver disease (NAFLD), resulting in liver cancer progression. Benzo(a)pyrene (B[a]P) is a common environmental and foodborne pollutant found in smoke and fire-grilled foods, which can have an adverse effect on human health. Hepatocellular carcinoma (HCC) is the fifth leading cause of cancer and the second leading cause of cancer-related deaths worldwide. The epidemiological studies suggest that both environmental risk factors and chronic liver injury including NAFL are important for HCC development, but the precise mechanisms linking eating habits to hepato-carcinogenesis remain unclear. In the present study, we demonstrated that various miRNAs in B[a]P-exposed tumor cells contribute to tumor metastasis, among which miR-650 could be the most potent inducer. Furthermore, we found that the suppressor of cytokine signaling 3 (SOCS3) is directly regulated by miR-650 and its suppression regulates the activation of the Janus kinase/signal transducer and activator of transcription 3 (JAK/STAT3) cascade. Our findings reveal a possible adverse outcome pathway of SOCS3/JAK/STAT3 regulation in B[a]P-induced HCC progress. These results provide a better understanding of the adverse effects of chronic exposure to B[a]P on human health.